2021
DOI: 10.1021/acsanm.1c02769
|View full text |Cite
|
Sign up to set email alerts
|

NaGdF4:Nd@NaGdF4 Core-Shell Down-Conversion Nanoparticles as NIR-II Fluorescent Probes for Targeted Imaging of Bacteria

Abstract: Bacterial infections are a serious ongoing threat to human health. As such, within the context of modern technology, there is an urgent need to develop fluorescent probes suitable for diagnosing bacterial infections in vivo. Herein, we synthesize NaGdF 4 :Nd@NaGdF 4 core-shell down-conversion nanoparticles (DCNPs) demonstrating excellent emission intensity in the second nearinfrared (NIR-II) window for use as fluorescent probes to enable high-quality imaging of pathogenic infections. The fluorescent probe is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Vancomycin (Van) is a Gram-positive antibiotic drug able to specifically bind with the D-Ala-D-Ala of bacterial cell walls, allowing it to guide nanomaterials for targeted drug delivery or imaging of bacterial inflammation in vivo. 28,29,51 The ability of Ag 2 S@ZIF-Van to target and detect bacteria was evaluated in vitro and in vivo. Incubation of S. aureus with Ag 2 S@ZIF-Van was followed by centrifugation and NIR-II fluorescence imaging.…”
Section: Targeting Imaging Of Bacterial Inflammation By Employing Ag ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Vancomycin (Van) is a Gram-positive antibiotic drug able to specifically bind with the D-Ala-D-Ala of bacterial cell walls, allowing it to guide nanomaterials for targeted drug delivery or imaging of bacterial inflammation in vivo. 28,29,51 The ability of Ag 2 S@ZIF-Van to target and detect bacteria was evaluated in vitro and in vivo. Incubation of S. aureus with Ag 2 S@ZIF-Van was followed by centrifugation and NIR-II fluorescence imaging.…”
Section: Targeting Imaging Of Bacterial Inflammation By Employing Ag ...mentioning
confidence: 99%
“…26,27 Fortunately, it has been found that vancomycin (Van) can guide a contrast agent to achieve targeted NIR-II fluorescent imaging in vivo at bacterial infection sites. 28,29 Biocompatible semiconductor Ag 2 S quantum dots (QDs), with a tunable fluorescence emission band from 800 nm to 1400 nm, have been widely used for basic medical analysis, 30,31 sensing, 32,33 and in vivo imaging and therapy. [34][35][36][37] Further, Ag 2 S QDs possess excellent photothermal conversion properties enabling their use as an antibacterial photothermal agent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescence reduction efficiency is estimated by (I 0 − I)/I 0 , where I 0 and I refer to 4f); the fluorescence response is found to be weaker for a small number of bacteria (<10 5 CFU). 40,41 For vancomycin-resistant Grampositive bacteria, vancomycin has a weak affinity to D-Ala-D- Ala residues on their surface, resulting in a relatively low fluorescence response. 42,43 Compared with PBS, Gramnegative bacteria can enhance the luminescence of DCNPs-Van/Cu 2−x Se by approximately a factor of 2, which is caused by the nonspecific binding of the positively charged DCNPs-Van moiety to the bacterial surface through electrostatic interaction.…”
Section: Synthesis Of Pss-capped Cu 2−mentioning
confidence: 99%
“…Nanoparticles (>10 nm) are known to primarily accumulate in the liver region, and the liver region exhibits a strong fluorescence signal. 41,48,49 The Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acssensors.2c00683.…”
Section: Synthesis Of Pss-capped Cu 2−mentioning
confidence: 99%